Exploring the structure of glass-forming liquids using high energy X-ray diffraction, containerless methodology and molecular dynamics simulation - Wilding, M; Benmore, C; Weber, R; Alderman, O; Tamalonis, A; McMillan, P; Wilson, M; Ribiero, M; Parise, J (Elsevier, 2019)
High energy X-ray diffraction can be combined with containerless techniques to provide information on the atomic arrangements in glass-forming liquids in stable and metastable regimes. The high incident energies provide bulk diffraction data to high values of scattering vector which enables significantly more robust analysis of the local and medium-range order that influences important physical properties such as viscosity and crystal nucleation. These combined techniques have been applied to a range of oxide liquids. In this contribution we illustrate addition of further dimensions to phase space by controlling the partial pressure of oxygen that permits the study liquids containing iron. The advantages of rapid data acquisition are also demonstrated in a study of tellurite glass-forming systems where a transition from ergodic to non-ergodic regimes in the deeply supercooled liquid is shown. Finally we demonstrate how descriptions of the liquid structure can be developed by combining HEXRD with molecular dynamics simulations.